2022
DOI: 10.1038/s41598-022-14894-4
|View full text |Cite
|
Sign up to set email alerts
|

A method for AI assisted human interpretation of neonatal EEG

Abstract: The study proposes a novel method to empower healthcare professionals to interact and leverage AI decision support in an intuitive manner using auditory senses. The method’s suitability is assessed through acoustic detection of the presence of neonatal seizures in electroencephalography (EEG). Neurophysiologists use EEG recordings to identify seizures visually. However, neurophysiological expertise is expensive and not available 24/7, even in tertiary hospitals. Other neonatal and pediatric medical professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In addition, the advancements in AI have continuously promoted the results of brain encoding and decoding, interpreting brain signals into text, vocal language, and images. For instance, the acoustic interpretation of EEG brain signals, converting EEG to sound using an AI-driven attention mechanism (Gomez-Quintana et al, 2022); the interpretation of human thoughts, captured via fMRI, into words by using GPT (Tang et al, 2023); and the reconstruction from EEG signals to corresponding images based on diffusion model (Zeng et al, 2023). Bringing together AI and cognitive science has thereby offered methods and approaches to study design from new perspectives.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…In addition, the advancements in AI have continuously promoted the results of brain encoding and decoding, interpreting brain signals into text, vocal language, and images. For instance, the acoustic interpretation of EEG brain signals, converting EEG to sound using an AI-driven attention mechanism (Gomez-Quintana et al, 2022); the interpretation of human thoughts, captured via fMRI, into words by using GPT (Tang et al, 2023); and the reconstruction from EEG signals to corresponding images based on diffusion model (Zeng et al, 2023). Bringing together AI and cognitive science has thereby offered methods and approaches to study design from new perspectives.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The authors demonstrated a significant correlation between positron emission tomography scan images and sonification spectrograms in healthy controls vs. patients with Alzheimer’s and frontotemporal dementia. Effective detection of critical events (neonatal seizures) was achieved by listening to an audio EEG signal generated by an AI-driven sonification algorithm [ 17 ]. This study showed that an hour of EEG could be analyzed in a very short time on the order of a few seconds.…”
Section: Introductionmentioning
confidence: 99%